AN ANALYSIS ON THE TRANSLATION OF DEFINITE AND INDEFINITE ENGLISH ARTICLE IN THE INDONESIAN VERSION OF A NOVEL - Florentina Suharjati (Deiksis, 2011)
This is a descriptive analytical study focusing in text analysis. The purpose of this study is to optain factual information concerning the translation of English articles into Indonesian in a novel “A Child Called It”. The problem of the study is how article as translated into Indonesian. The result of the analysis revealed that the numbers of English articles under study were 745, but not all of them were translated, namely 71.1%. Of these, which were translated, consisted of 15.2% definite article and 13.7% indefinite ones. The finding of this study showed that in line with the theory of articles and artikula most of these articles were not translated.Key Word: translation, definite and indefinite articles.